The role of deformation history on stress relaxation and stress memory of filled rubber - Fernandes Arruebarrena, Vanessa Auxiliadora; De Focatiis, Davide S.A. (Elsevier, 2014)
Although the magnitudes of inelastic and viscoelastic effects in filled rubbers are small relative to that of the elastic response, these effects are nevertheless critical in applications such as gaskets, seals and dampers. This study investigates the role of deformation history on relaxation of rubber through time-dependent experiments following a range of deformation histories. Two grades of carbon-black filled EPDM were subjected to uniaxial tensile deformation followed by stress-relaxation or stress memory at fixed deformation. Stress relaxation was found to be highly dependent on strain levels following a single loading. When an additional load-unload cycle was added to the history, the rubbers relaxed an approximately constant fraction of stress after a given time, provided that the strain at stress relaxation was smaller than the historical maximum. This fraction was independent of both the applied strain and of the maximum strain, and suggests that the relaxation process is independent of scragging procedures used to control the modulus. Stress memory observed following load-unload cycles was also approximately independent of strain history.